Norias, boreholes and the role of the state during the groundwater ‘silent revolution’ in La Mancha, Spain - Closas, Alvar (Springer, 2014)
The ‘silent revolution’ is a phenomenon describing the individualistic behaviour of farmers in the adoption of intensive groundwater abstraction technologies, which in some cases has led to groundwater over-abstraction and environmental degradation in semiarid areas such as La Mancha, Spain. However, a lacuna exists as to the extent to which state politics have affected the development of groundwater abstraction technologies in Spain. With new quantitative and qualitative data from the irrigation community of Manzanares and public irrigation and colonisation plans, this report studies the adoption of groundwater abstraction technology and investigates the historical role of the state in the development of modern groundwater-fed irrigation socio-ecologies in the semiarid area of La Mancha in Spain.